Asesmen Self-Efficacy Konselor dalam Konseling : Pengembangan dan Validasi - Fitri Wahyuni; Citra Kurniawan (Kuras Institute, 2022)
Counselor self-efficacy in counseling is one of the variables that affect the performance and outcomes of counseling. A number of studies have proven the importance of counselor self-efficacy in implementing counseling. However, in Indonesia there is no instrument that measures the counselor's self-efficacy in implementing counseling. This study aims to develop and validate the counselor's self-efficacy scale in counseling. The counselor's self-efficacy scale in counseling was developed to assess the counselor's belief in counseling. The scale was developed based on the skills used in the counseling phase in general. The counselor's self-efficacy scale in counseling consists of 3 dimensions with 26 statement items. The subjects of this study were school counselors throughout Malang Raya with 100 school counselors as participants. The procedure for compiling the instrument consists of four steps; define constructs, develop measurement models, perform confirmatory factor analysis and check the validity of the measurement models. Reliability Test using Cronbach's Alpha and Reliability Construct. The results of the research analysis show that the counselor's self-efficacy scale in counseling (SEKDK) is valid and reliable